Social problems and its relationship with family institution in FELDA settlements: the local perspectives - Ismail, Nik Ahmad Hisham; Kamaruddin, Zaleha; Nordin, Mohamad Sahari (EuroJournals Publishing, Inc., 2010)
Malaysia is targeted to be an industrialized nation by year 2020. In this context, FELDA has been identified as a new industrialized town in order to achieve part of this ambition. The absence of a balanced development would- lead to negative effects which in the longrun might affect the target and the future planning of the nation. Among the main objectives of this research are: to identify what are the types of social problems in FELDA; to find the root of cause those problems from the local perspective; and to propose dysfunction as well as to draw up a few steps or measures on how to overcome them. Results of the research are as follows: i) many respondents stated that their parents were the cause of moral decadence; ii) Drugs abuse was also associated with the increase in crimes; vi) the level of academic achievements of the early settlers’ children was also not very encouraging; vii) attitude of putting too much emphasis on materialism amongst parents were said to have been the main cause of their children getting little or no religious education; and viii) parents’ attitude of not taking seriously any wrongdoings of their children. The research suggests as follows: i) effort and cooperation of various parties including the leaders, the schools, and the authorities the religious departments as well as the management of FELDA are important; ii) parents must be firm in nurturing and educating their children; iii) the empowerment and the implementation of laws should be emphasized especially by the Police; iv) awareness of religion also plays a very important role in the lives of human beings; v) schools are to be pro-active in solving the social and disciplinary problems amongst students.